2017
DOI: 10.1002/ecy.1998
|View full text |Cite
|
Sign up to set email alerts
|

ATLANTICCAMTRAPS: a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America

Abstract: Abstract. Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…Altogether, we compiled data on 1,831 species occurring in 1,953 sampling sites, totalling nearly 59,000 species occurrence records (Figure ). The data were collected between years 1990 and 2017, during which the geographical coordinates are of required accuracy (Bovendorp et al, ; Culot et al, ; Hasui et al, ; Lima et al, ; de Lima et al, ; Muylaert et al, ). A list of the filtered tree data sources is found in Appendix , Table .…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, we compiled data on 1,831 species occurring in 1,953 sampling sites, totalling nearly 59,000 species occurrence records (Figure ). The data were collected between years 1990 and 2017, during which the geographical coordinates are of required accuracy (Bovendorp et al, ; Culot et al, ; Hasui et al, ; Lima et al, ; de Lima et al, ; Muylaert et al, ). A list of the filtered tree data sources is found in Appendix , Table .…”
Section: Methodsmentioning
confidence: 99%
“…In doing so, we initially used data of mammal assemblages throughout the entire Atlantic Forest, spanning parts of Brazil and Argentina, contained in Canale et al (2012), Bogoni et al (2017) and Lima et al (2017). adult body mass ≥ 1 kg) studies across the entire Atlantic Forest biome using search engines.…”
Section: Mammalian and Dung Beetle Assemblagesmentioning
confidence: 99%
“…We also searched for papers not indexed by 'Web of Science' and from gray literature, such as dissertations, reports and monographs. We included studies with lists of medium and large mammals, irrespective of survey methods used (Lima et al 2017). A complete list of studies can be found in Supplementary material Appendix 1.…”
Section: Medium and Large Mammal Assemblagesmentioning
confidence: 99%